A randomized trial to determine whether wearing slippers reduces transfer of bacteriophage MS2 from floors to patients and surfaces in hospital rooms. (23rd April 2023) - Haq, Muhammed F.; Alhmidi, Heba; Redmond, Sarah N.; Cadnum, Jennifer L.; Silva, Sandra Y.; Wilson, Brigid M.; Donskey, Curtis J.
Abstract: In a randomized trial, patients wearing slippers whenever out of bed transferred bacteriophage MS2 from hospital room floors to patients and surfaces significantly less often than controls not provided with slippers. Wearing slippers could provide a simple means to reduce the risk for acquisition of healthcare-associated pathogens from contaminated floors. Registration: ClinicalTrials.gov; NCT04935892